Media selling digital, television, audio, print and cross-platform - Warner, Charles 1932-; Lederer, William A.; Moroz, Brian (Wiley Blackwell, 2020)
Updating the 4th Edition of Media Selling, published in 2009, has been challenging because of the exponential changes in the media, especially in digital advertising, which in 2016 toppled television as the number-one advertising medium, and in the time since the 4th Edition, Google and Facebook have dominated the digital advertising media environment. In 2016 and 2017 the two Internet giants amassed approximately 90 percent of the increase in digital advertising investment over the previous year, leaving hundreds of thousands of advertising-supported websites and apps struggling to survive by dividing the crumbs of the remaining ten percent of the digital advertising yearly increase. It is difficult to keep up with accelerating changes in the media and in advertising because these changes are driven mostly by advances in artificial intelligence (AI), but this edition includes many of the changes up until August of 2019. With that in mind, we (the authors) have tired to avoid predicting the future beyond 2019. We have also listed for readers the URLs of websites and industry newsletters, blogs, apps, and websites where they can keep up to date on current information-- Provided by publisher.